PLAIDOH: a novel method for functional prediction of long non-coding RNAs identifies cancer-specific LncRNA activities - Pyfrom, Sarah C.; Luo, Hong; Payton, Jacqueline E. (BMC genomics, 2019)
Background Long non-coding RNAs (lncRNAs) exhibit remarkable cell-type specificity and disease association. LncRNA’s functional versatility includes epigenetic modification, nuclear domain organization, transcriptional control, regulation of RNA splicing and translation, and modulation of protein activity. However, most lncRNAs remain uncharacterized due to a shortage of predictive tools available to guide functional experiments. Results To address this gap for lymphoma-associated lncRNAs identified in our studies, we developed a new computational method, Predicting LncRNA Activity through Integrative Data-driven ‘Omics and Heuristics (PLAIDOH), which has several unique features not found in other methods. PLAIDOH integrates transcriptome, subcellular localization, enhancer landscape, genome architecture, chromatin interaction, and RNA-binding (eCLIP) data and generates statistically defined output scores. PLAIDOH’s approach identifies and ranks functional connections between individual lncRNA, coding gene, and protein pairs using enhancer, transcript cis -regulatory, and RNA-binding protein interactome scores that predict the relative likelihood of these different lncRNA functions. When applied to ‘omics datasets that we collected from lymphoma patients, or to publicly available cancer (TCGA) or ENCODE datasets, PLAIDOH identified and prioritized well-known lncRNA-target gene regulatory pairs (e.g., HOTAIR and HOX genes, PVT1 and MYC), validated hits in multiple lncRNA-targeted CRISPR screens, and lncRNA-protein binding partners (e.g., NEAT1 and NONO). Importantly, PLAIDOH also identified novel putative functional interactions, including one lymphoma-associated lncRNA based on analysis of data from our human lymphoma study. We validated PLAIDOH’s predictions for this lncRNA using knock-down and knock-out experiments in lymphoma cell models. Conclusions Our study demonstrates that we have developed a new method for the prediction and ranking of functional connections between individual lncRNA, coding gene, and protein pairs, which were validated by genetic experiments and comparison to published CRISPR screens. PLAIDOH expedites validation and follow-on mechanistic studies of lncRNAs in any biological system. It is available at https://github.com/sarahpyfrom/PLAIDOH .